Unusual Presentation of an Uncommon Disease: 24-Hour Cyclic Esotropia - Miguel Paciuc-Beja; Victor Hugo Galicia-Alfaro; Myriam Retchkiman-Bret (Case Reports in Ophthalmological Medicine)
Cyclic esotropia is an extremely uncommon form of strabismus. Classically, it follows a 48-hour cycle with 24 hours of orthotropia and 24 hours of manifest esotropia. We are reporting the first case of cyclic esotropia with a 24-hour cycle. A 7-year-old hyperopic female was seen with an esotropia of 6-month duration. Hyperopic glasses were prescribed by another ophthalmologist prior to our evaluation of the patient. While wearing her glasses, esotropia occurred during the morning and early afternoon. After 3.00pm, her eyes were “straight.” Many photographs were reviewed, confirming the esotropia pattern. Neurological evaluation was normal, including imaging and blood work to rule out thyroid pathology and myasthenia. After seeing the patient multiple times at different hours on different days, the diagnosis of cyclic esotropia was made. Bimedial recessions were performed with good results. The patient was still “straight” at distance and near 2 years after surgery.